Hadits Prespektif Fazlur Rahman: Pencandraan Epistemologis Filsafat Ilmu Fazlur Rahman Atas Hadits - Masyhadi Masyhadi (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2017)
Fazlur Rahman's view brings logical consequence, that is, it is necessary to understand the Prophet's behavior in the frame of context and its sociological-historical framework. In other words, the sunnah of the prophet needs to be regarded as an example, not as an absolute special content.